Stress and hope distinguish individuals with suicidal plan from suicide ideators among Chinese college students - Chen, Naiche; Dai, Zheru; Wang, Yongguang (Frontiers in Psychiatry, 2024)
Suicide among college students is a significant public health concern in China. While suicidal ideation serves as a crucial predictor of subsequent suicidal plans and behaviors, it is important to recognize that most instances of suicidal ideation may only be fleeting thoughts that do not progress to an actual plan.Therefore, it is imperative to identify the factors associated with the transition from suicidal ideation to a concrete plan. Consequently, this study aims to investigate whether certain frequently cited factors can differentiate individuals who have formulated a specific suicidal plan from those who have experienced suicidal thoughts without planning, based on data obtained through a cross-sectional survey.: This survey was conducted as part of routine mental health assessments among second-year college students in October 2023. Data from a total of 4858 second-year college students were utilized for the final analyses. Two survey questions were employed to identify past-year suicidal ideation and past-year suicidal plan. All participants were required to complete various assessments, including the Chinese version of Depression Anxiety Stress Scale 21 items (DASS-21), the Chinese version of Gratitude Questionnaire-six items (GQ-6), the Chinese version of Meaning in Life Questionnaire (MLQ), and the Chinese version of State Hope Scale (SHS).Results: Amongst 4858 participants, a total of 134 individuals (2.8%) were confirmed to have experienced past-year suicidal ideation. Out of these, fifty-three (1.1% overall) reported having a past year suicidal plan, accounting for approximately 39.6% of those with suicidal ideation. Logistic regression analyses revealed that while most potential variables differentiated between students with and without suicidal ideation, only two factors stood out in distinguishing individuals with a suicidal plan from those who had not made such plans despite experiencing suicidal thoughts -presence of stress (OR=2.49, 95%CI:1.04-5.96) and lower scores of hope agency (OR=0.84, 95%CI:0.72-0.98).These findings suggest that the stress may contribute to susceptibility for transitioning from mere thoughts to actual planning regarding suicide; conversely, hope agency appears to offer protection against this transition process. Therefore, we advocate for targeted interventions aimed at fostering hope among individuals who have encountered adverse and stressful life events.